Parasitic necrotizing pneumonia in an immunocompetent patient in United States. Issue 1 (2nd January 2021) - Gopalakrishna, Harish; Nair, Gayatri B.; Conti, Ricardo
ABSTRACT: A 59-year-old Baltimore native female, with a history of asthma and no history of travel outside of the USA, presented with productive cough and shortness of breath. Computed tomography scan showed left upper lobe consolidation of the lung with multiple tiny cavitations. She was empirically treated without improvement. Later, strongyloides were found in the sputum gram stain and she was treated with ivermectin. Pulmonary strongyloidiasis has been mainly described in patients who are immunosuppressed and have a history of travel to endemic areas, both of which were absent in our patient. Our case underlines the importance of considering strongyloides necrotizing pneumonia as a differential diagnosis of community-acquired pneumonia even in immunocompetent patients in the USA, especially if not responding to empiric treatment.